Boldly Going Vegan? Star Trek, Synthetic Meat, and Animal Ethics. - Bulleid, Joshua (Science Fiction Studies, 2022)
This article examines the engagements with veganism, synthetic food, and animal ethics throughout Star Trek's seven live-action incarnations: The Original Series (TOS, 1966-1969), The Next Generation (TNG, 1987-1994), Deep Space Nine (DS9, 1993-1999), Voyager (1995-2001), Enterprise (2001-2005), Discovery (2017-), and Picard (2020-). I show how the separate Star Trek series maintain regular rhetorical gestures toward veganism as an ethically enlightened practice and philosophy in the framework of an influential engagement with synthetic food technology that allows for traditional, omnivorous meals without the need of nonhuman animal suffering. Star Trek's human characters, however, also frequently emphasize "real" food--especially meat--in connection with nostalgic Anglo-American values and supposedly superior "natural" living, so that meat-eating also often reflects notions of imperialism, colonization, and masculinity. Human meat-eating is also frequently represented as a sensible medium between violent, uncivilized carnism and an overly repressive veganism that is further exoticized by its associations with non-human and allegedly un-American cultures. Only the current series Discovery (2017-) takes veganism seriously as a core utopian value, due to the emphasis it places on interspecies relationships.